A Low-distortion Hardware Efficient MASH Modulator with Enhanced Noise Shaping. Issue 2 (3rd April 2018) - Sebastian, Rijo; Jose, Babita Roslind; Shahana, T. K.; Mathew, Jimson
Abstract: This paper proposes an improved multi-stage noise shaping modulator architecture that can attain an enhanced noise shaping through analog inter-stage feedback paths. The elimination of the feed-forward adder before the quantizer in the first stage and enhanced noise shaping without any increase in the number of active blocks makes this architecture hardware efficient. The shifted loop delay techniques utilized in this architecture helps to relax the signal processing timing issues in digital to analog conversion and dynamic element matching process. The low-distortion architecture in both stages of MASH structure reduces the integrator associated non-idealities. The resolution of this modulator is further improved by noise transfer function zero optimization methods. The low-distortion architecture, selection of low oversampling ratio, fewer number of adder and active blocks and achievement of fourth-order noise transfer function makes this modulator suitable for low power wideband applications. The behavioral simulations and mathematical analysis confirm the effectiveness of this proposed modulator. Graphical Abstract: